Exercise 'Technology Assessment' through a gaming procedure. (27th November 2006) - Ahamer, Gilbert; Schrei, Christian
How to train advanced university students for 'Technology Assessment' (TA)? Which type of social process design is best for learning social and academic skills? A new negotiation game ('Surfing Global Change') tries to give an answer. Its graphic design elements represent the underlying e-learning concept. Analysis highlights the importance of rhythmisation in the social processes in order to safeguard training efficiency for different initial levels of proficiency in a class. Multi-perspectivism is facilitated by taking roles of different stakeholders. We understand 'design' in a universal way as a compound of temporal, spatial and inter-individual structures facilitating the realisation of processes.